2018
DOI: 10.1111/and.13154
|View full text |Cite
|
Sign up to set email alerts
|

The appropriate number of negative lymph nodes dissection for nonmetastatic penile cancer

Abstract: Negative lymph nodes status has been attached more attention as a prognostic indicator for nonmetastatic penile cancer. We aimed to identify the appropriate number of negative lymph nodes dissection for nonmetastatic penile cancer using the Surveillance, Epidemiology and End Results database. A total of 1,470 nonmetastatic patients with penile squamous cell carcinoma were identified during 2004 and 2013. All patients were categorised according to different risk levels and lymphadenectomy. Univariate and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Such patients might also benefit from early lymphadenectomy or sentinel lymph node biopsy. Indeed, several studies have shown a significant survival benefit for patients with nonmetastatic high-risk PC when early lymphadenectomy is performed [37].…”
Section: Discussionmentioning
confidence: 99%
“…Such patients might also benefit from early lymphadenectomy or sentinel lymph node biopsy. Indeed, several studies have shown a significant survival benefit for patients with nonmetastatic high-risk PC when early lymphadenectomy is performed [37].…”
Section: Discussionmentioning
confidence: 99%